TRADITIONAL UZBEK WOMEN’S CLOTHING: FABRICS, EMBROIDERY, AND CULTURAL SIGNIFICANCE - Ochilova Marjona O‘tkir qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: This article examines the cultural and artistic significance of traditional Uzbek women’s clothing, focusing on the use of atlas and adras fabrics. It explores the role of embroidery, zardozi (gold-thread work), and pattern composition in creating garments that reflect regional identity and social status. The study also highlights the integration of modern techniques in preserving traditional craftsmanship while adapting garments for contemporary fashion.